One Social Media Company to Rule Them All: Associations Between Use of Facebook-Owned Social Media Platforms, Sociodemographic Characteristics, and the Big Five Personality Traits - Marengo, Davide; Sindermann, Cornelia; Elhai, Jon D.; Montag, Christian (Frontiers in Psychology, 2020)
Currently 2.7 billion people use at least one of the Facebook-owned social media platforms - Facebook, WhatsApp and Instagram. Previous research investigating individual differences between users and non-users of these platforms has typically focused on one platform. However, individuals typically use a combination of Facebook-owned platforms. Therefore, we aim 1) to identify the relative prevalence of different patterns of social media use, and 2) to evaluate potential between-group differences in the distributions of age, gender, education and Big Five personality traits. Data collection was performed using a cross-sectional design. Specifically, we administered a survey assessing participants’ demographic variables, current use of Facebook-owned platforms and Big Five personality traits. In N=3003 participants from the general population (60.6% females; mean age = 35.53 years, SD=13.53), WhatsApp emerged as the most widely used application in the sample, hence, having the strongest outreach. A pattern consisting of combined use of WhatsApp and Instagram appeared to be most prevalent among the youngest participants. Further, individuals using at least one social media platform were generally younger, more often female and more extraverted than non-users. Small between-group differences in Conscientiousness and Neuroticism also emerged. Interestingly, when examined as control variables, we found demographic characteristics partially accounted for differences in broad personality factors and facets across different patterns of social media use. Our findings are relevant to researchers carrying out their studies via social media platforms, as sample characteristics appear to be different depending on the platform used.